CONSEQUENCES OF PSYCHOLOGICAL VIOLENCE AGAINST WOMEN (E Conference Zone, 2022)
This article discusses the fact that victims of psychological and physical violence are often victims of economic violence, i.e. they cannot find the funds to escape the situation they are in and receive free psychological assistance at counters and women's listening centers. are analyzed.